Moksha for Modiaain: A Study of B. P. Koirala’s Modiaain - Nitya Raj Bhattarai, (Journal of Business and Social Sciences, 2023)
Bisheswor Prasad Koirala’s Modiaain is a novella written on the war of Mahabharat, the 18 days fratricidal war between Kaurabh and Pandava, in Hindu mythology. The two supreme Hindu religious volumes, Mahabharat and SrimadBhagawat Gita, glorify the war and claim that it was fought for justice and righteousness led by the god, lord Krishna, himself. However, Modiaain, the title character whose husband fought the war from the Kaurabh’s side, has her own interpretation of the war as she mentions it to the narrator. She finds the role of Lord Krishna controversial, in the war, as he incites Arjuna for the war to save humanity from irreligiosity. The paper studies the difference between the presentation of these holy text by the gods (Ved Vyas and Lord Krishna) and a common woman (Naari). Several incidents in the novel, as reported by Naari, exposes the effect of the war not only to the warriors but also to their families. Many of them died waiting and crying on the loss of their dear ones- and are still living as degenerated spirit hovering here and there around the battlefield. In its thorough analysis of the events, in the perspective of the renarrative of Karma and Moksha, the research locates the disparity and questions the mere promise and purpose of lord Krishna behind the war. Clearly, the article focuses on to draw out a new perspective to read and interpret the ideas of these holy texts- not to criticize them in a biased way.